2018
DOI: 10.3390/met8090696
|View full text |Cite
|
Sign up to set email alerts
|

Study on Fracture-Split Performance of 36MnVS4 and Analysis of Fracture-Split Easily-Induced Defects

Abstract: The material 36MnVS4 is the second generation of connecting rod fracture-split material. However, it generates more quality defects during the fracture-split process. To investigate the causes of defects that occurred, the material properties and fracture-split performance of the 36MnVS4 are researched and compared with C70S6. The fracture-split easily-induced defects are also analyzed. By finite element simulation and experimental analysis, the results show that the 36MnVS4 has lower carbon content and more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The martensitic steel achieved higher strengths (YS: 847 MPa) and the impact toughness reached values above 30 J, which is required for most automotive chassis application [9]. However, due to the partly ductile fracture, quality issues might occur during the splitting process [17,18]. Both materials offer the possibility to reduce the CO 2 -footprint of con-rods, either by lightweighting or by a reduction of the heat treatment, if quench and tempering steels are substituted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The martensitic steel achieved higher strengths (YS: 847 MPa) and the impact toughness reached values above 30 J, which is required for most automotive chassis application [9]. However, due to the partly ductile fracture, quality issues might occur during the splitting process [17,18]. Both materials offer the possibility to reduce the CO 2 -footprint of con-rods, either by lightweighting or by a reduction of the heat treatment, if quench and tempering steels are substituted.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was demonstrated that the die-forged steels have a much higher fatigue resistance than the sinter components, which prohibited the broad application of this elaborate process [13]. As con-rods are produced by fracture-splitting [15][16][17], the fracture behaviour of steels for this application needs to be investigated. Contrary to other applications, the material needs to split in a brittle manner, as ductile deformation might lead to quality issues [17,18] or completely prevent the splitting process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These induced harmful residual tensile stresses resulting in early fatigue failure [6]. An analysis of the failuresplit performance of 36MnVS4 detected defects [7]. To investigate the causes of defects that occurred, the material properties and fracture-split performance of the 36MnVS4 are researched and compared with C70S6.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have been focused on the failures of rods, which in turn caused engine catastrophic failures; regarding this point, a large collection of failures involving connecting rods (con-rods) is, for instance, provided in [1]. A detailed analysis of con-rod states of load and stress is delivered in [2], whereas, again with reference to this component, focus is placed on static and dynamic material properties in [3][4][5]. The primary reasons for rod breakage were mainly related to fatigue cycling that triggered crack initiation in zones with too high stress concentrations owing to poor design [6].…”
Section: Introductionmentioning
confidence: 99%